Biofunctionalization of Nerve Interface via Biocompatible Polymer-Roughened Pt Black on Cuff Electrode for Chronic Recording - Lee, Yi Jae; Kim, Han-Jun; Kang, Ji Yoon; Do, Sun Hee; Lee, Soo Hyun (WILEY, 2017)
Peripheral nerve cuff electrodes with roughened Pt black (BPt) are coated with polyethylene glycol (PEG) and Nafion (NF). Although the influence of coated PEG and Nafion on roughened BPt on the electrical properties is weak, the cuff electrode with BPt/PEG and BPt/Nafion exhibits some very important properties. For example, it markedly decreases interfacial impedance, increases charge storage capacity (CSC) due to retaining the BPt surface structure, good stability without exfoliation in repetitive cyclic voltammetry scanning because it is protected by PEG or Nafion coating. In cell viability test, Nafion-coated BPt does not show cytotoxicity to rat Schwann cell line (S16) at 24 and 72 h with the Nafion coating ranging from 0.1 to 10 mg cm(-2). In addition, real-time polymerase chain reaction (PCR) analysis indicates that Schwann cell differentiation (S100 calcium-binding protein B, myelin basic protein, peripheral myelin protein 22), proliferation (proliferating cell nuclear antigen, cyclin-dependent kinase 1 (CDK1)), and adhesion molecules (neural cell adhesion molecule, laminin, fibronectin) are upregulated up to 5 mg cm-2 of Nafion. In animal study, the BPt/Nafion reduces infiltration of fibrotic tissue with high axonal maintenance with upregulation of proliferation (CDK1), adhesion (laminin, neuronal cell adhesion molecule), and neurotrophic factor receptor-related (gdnf family receptor alpha 1) mRNA expressions.
Keywords: IN-VITRO; HYDROGEL COATINGS; CELL; REGENERATION; SURFACE; PERFORMANCE; NANOTUBES; IMPROVE; LAMININ; MODEL